Trends in the incidence and mortality of kidney cancer in Lithuania from 1993 to 2012 - Patašius, Aušvydas; Ulytė, Agnė; Ulys, Albertas; Smailytė, Giedrė (Acta medica Lituanica, 2019)
Background. The aim of this paper is to analyse trends of kidney cancer incidence and mortality in Lithuania during the period of 1993 to 2012 using joinpoint regression models with special attention to changes in the distribution of stages. Materials and methods. The study was based on all cases of kidney cancer reported to the Lithuanian Cancer Registry between 1993 and 2012. Age group-specific rates and standardized rates were calculated for each sex, using the direct method (world standard population). The joinpoint regression model was used to provide the estimated annual percentage change and to detect points in time where significant changes in the trends occur. Results. During the study period the age-standardized incidence rates increased from 16.89/100,000 in 1993 to 27.77/100,000 in 2012 in males, and from 7.95/100,000 to 13.44/100,000 in females. During this period, annual percentage changes in the age-standardized rates were 2.33% and 1.81% for males and females, respectively. The joinpoint analysis by stage of disease showed the highest increase in stage I kidney cancer, with statistically significant trend change in 2002 for males and in 2001 for females. During the study period, age-standardized mortality rates decreased from 10.42/100,000 in 1993 to 8.96/100,000 in 2012 in males, and from 4.54/100,000 to 3.9/100,000 in females. Conclusions. The kidney cancer incidence rate in Lithuania rose during the period of 1993 to 2012. The detailed analysis by stage showed the most significant increase in organ-confined incidence of kidney cancer. A stable mortality trend for males and a decreasing mortality trend for females along with increased incidence of early stage kidney cancer indicate that both earlier detection and modern treatment modalities may contribute to the reduction of mortality.